Sustainability assessment of large-scale composting technologies using PROMETHEE method - Makan, Abdelhadi; Fadili, Ahmed (Journal of cleaner production, 2020)
Composting is considered as a sustainable strategy for organic waste management, yet the choice of suitable technology makes its sustainability disputable. The subject under investigation concerns the sustainability assessment of large-scale composting technologies using surrogate weights and PROMETHEE method. In this regard, six composting systems, including open, enclosed and reactor technologies, were evaluated in terms of environmental, financial/economic, social and technical criteria. Firstly, ten internationally endorsed experts assigned their preferred rankings for the groups of criteria as well as the sub-criteria. The application of the additive combination of sum and reciprocal weight functions on these rankings allowed calculating the corresponding weights for each group of criteria and each sub-criterion. Secondly, the PROMETHEE method was applied, taking into account the alternatives’ performance with regards to each criterion, to calculate the outranking flows for each alternative. The obtained rankings revealed that reactor technologies are more sustainable than enclosed technologies, which in turn are more sustainable than open technologies. Overall, the rotating drum is ranked as the most sustainable composting technology achieving the optimal balance among the environmental, financial/economic, social, and technical criteria. However, the turned windrow seems to be the least sustainable composting technology. [Display omitted] •Sustainability assessment of large-scale composting technologies was investigated.•Surrogate weights and PROMETHEE method were used.•Environmental, economic, social and technical criteria were considered.•Reactor technologies are more sustainable than enclosed and open technologies.•Rotating drum achieved the optimal balance among the considered criteria.